Late Pleistocene subsistence in the Great Basin: Younger Dryas-aged faunal remains from the Botanical Lens, Paisley Cave 2, Oregon. (June 2017) - Hockett, Bryan; Adams, Martin E.; Lubinski, Patrick M.; Butler, Virginia L.; Jenkins, Dennis L.
Highlights: Paisley Cave 2 preserves a short-term record of human subsistence ca. 12, 200 cal. BP. During the Younger-Dryas, hunter-gatherers consumed pronghorn, jackrabbits, fish, and insects. These data suggest that Paleoindian hunter-gatherers in the Great Basin were not the "big-game" hunters of folklore.